The Method Of Taskhir Al-Qur’an As Islamic Hypnotherapy Study Of Living Qur'an In Jam'iyyah Ruqiah Aswaja Bekasi Branch - Muhamad Azizan Fitriana; Ade Naelul Huda; Sa'id al-Khudry (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This article aims to reveal the merger between two therapeutic methods used by the Jam’iyyah Ruqyah Aswaja (JRA) in Bekasi, namely the ruqyah method and the hypnotherapy method. The tendency of people to switch from medical medicine to alternative medicine is very high. So came various techniques and methods of alternative medicine that are popular with the community, including ruqyah which has been very popular among Muslims. Unlike ruqyah which is identical to Islam, hypnotherapy is a method that is born not from a certain belief background. This relatively new medical technique can be practiced by anyone with any religious background. Because it is considered not to disturb the creed, the idea arose to combine ruqyah with hypnotherapy. Among the communities that developed a combination of these two alternative methods is Jam'iyyah Ruqyah Aswaja Bekasi Branch which introduced Islamic hypnotherapy with the Taskhir al-Qur’an method. This study used qualitative methods to analyze field data taken using observation techniques and depth interviews. The results of this study show that Jam'iyyah Ruqyah Aswaja Bekasi states that the Taskhir al-Qur’an method can be used to treat psychic and physical. The process of handling patients begins with hypnotherapy techniques, after the patient enters the subconscious recited verses of the Qur'an which indicate the process of ruqyah has begun. Taskhir al-Qur’an method has four approaches, namely: Taskhir al-Nidzam for physical and psychological disorders; Taskhir al-Qulub for mental balance disorders; Taskhir al-Gharib for telemedicine; and Taskhir al-Ghoibi for mass treatment services for all complaints experienced by patients.